Workload measures—recent trends in the driving context - Costa, Nélson Bruno Martins Marques da (2019)
This work is the follow-up of previous research where the authors postulated the need for the establishment of a standardized methodology for assessing the driver’s workload, given its importance in the driving context and the upcoming shift in the driving paradigm, namely the widespread use of conditional autonomous vehicles. Even though the early research devoted to this matter was somewhat scattered, a bottleneck in the scope of the dedicated literature seemed to begin to appear in the latter years. As such, the authors aimed to search for the trends in the use of workload measures within this scope, in a recent timeframe. Indeed, this convergence may unveil eventual best practices resulting from the researchers’ effort to cope with this recognized handicap in the decision on the best choice regarding workload measures. The results obtained are believed to be indicative of the best path for the standardisation of the method. A systematic literature review was conducted and it was found that there is a growing tendency to simultaneously apply all three workload measures (subjective, physiological and performance), as means to achieve redundant, comparable and more reliable results. Among the specific measures of workload, the most frequently used subjective measure is the NASA-TLX, whereas the HR-related measures are the most frequently used among the physiological measures and the most frequent performance measure is the primary driving task activity.